Enhancing fiqh learning achievements: Integrating Project-Based Learning with Android applications - Imtihanah, Imas Masruroh; Nurhayati, Nurhayati; AG, Huliman; Waehama, Muhammad Roflee (International Journal of Nusantara Islam, 2025)
This study was prompted by the low learning achievement in Fiqh among students at Madrasah Aliyah, as indicated by preliminary data showing that only about 70% of students in several grade X classes reached the minimum mastery criteria (KKM), set at a score of 75. To address this issue, the study aims to analyze needs, design, develop, implement, and evaluate the effectiveness of an Android-based Project-Based Learning (PJBL) application called MaBar FIQIH in improving Fiqh learning outcomes for grade X students at MAN 2 Bandung and MAS Baitus Shofaa Ciheulang Bandung. The research used a Convergent Parallel Mixed Method approach and the Research and Development (R&D) method, applying the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects included media and content experts, as well as 355 students from MAN 2 Bandung and 150 students from MAS Baitus Shofaa. Implementation results showed that the application had a significant effect on students’ learning achievements. There was a significant difference in students’ learning achievements after the use of the MaBar FIQIH application. The findings suggest that this PJBL-based application is effective and feasible for use by teachers and students in enhancing Fiqh learning outcomes.